Surfactant‐Assisted Stabilization of Au Colloids on Solids for Heterogeneous Catalysis. (22nd March 2017) - Zhan, Wangcheng; Shu, Yuan; Sheng, Yujie; Zhu, Huiyuan; Guo, Yanglong; Wang, Li; Guo, Yun; Zhang, Jinshui; Lu, Guanzhong; Dai, Sheng
Abstract: The stabilization of surfactant‐assisted synthesized colloidal noble metal nanoparticles (NPs, such as Au NPs) on solids is a promising strategy for preparing supported nanocatalysts for heterogeneous catalysis because of their uniform particle sizes, controllable shapes, and tunable compositions. However, surfactant removal to obtain clean surfaces for catalysis through traditional approaches (such as solvent extraction and thermal decomposition) can easily induce the sintering of NPs, greatly hampering their use in synthesis of novel catalysts. Such unwanted surfactants have now been utilized to stabilize NPs on solids by a simple yet efficient thermal annealing strategy. After being annealed in N2 flow, the surface‐bound surfactants are carbonized in situ as sacrificial architectures that form a conformal coating on NPs and assist in creating an enhanced metal‐support interaction between NPs and substrate, thus slowing down the Ostwald ripening process during post‐oxidative calcination to remove surface covers.